When is parenteral nutrition indicated in the hospitalized, acutely ill patient?. Issue 2 (March 2020) - Fragkos, Konstantinos C.; Sebepos-Rogers, Gregory; Rahman, Farooq
Abstract : Purpose of review: The current review discusses current practices regarding appropriate indications for parenteral nutrition in acutely ill hospitalized patients. We address-specific indications for parenteral nutrition in the perioperative period, and in inflammatory bowel disease, oncology, hepatobiliary, critical care and end-stage renal disease patients. Recent findings: Acutely ill hospitalized patients can develop intestinal failure requiring parenteral nutrition. Recent studies have provided insight into the main indications. The most common indications for inpatient parenteral nutrition include postsurgical complications, including prolonged ileus, sepsis, fistula and leaks, and bowel obstruction, predominantly malignant. Severe or complicated inflammatory bowel disease and cancer treatment-related mucosal enteropathies (mucositis, enterocolitis, gut graft-versus-host disease) are the next commonest indications. Less frequent indications are primary motility disorders and inability to secure enteral access for enteral nutrition. Gastrointestinal failure of the intensive care patient is a separate entity resulting from multiple mechanisms, including an enteropathy and dysmotility. Summary: Despite the wider availability of nutrition support teams, use of parenteral nutrition is not without risk. The risks and benefits of parenteral nutrition in the acute setting need to be carefully considered even when it is indicated.